بعض الإشارات القرآنية في الجيولوجيا والجيومورفولوجيا (Albayan Scientific Journal, 2023)
recent times, due to the amazing scientific discoveries made by mankind in this time, but clear references to it were found in the Holy Book more than 1400 years ago from now. This revelation was revealed to our Prophet Muhammad, peace and blessings be upon him, and it served as an extremely accurate scientific basis for describing these natural phenomena of the planet. Consequently, the research problem was determined by whether there is a scientific relationship between what came in the book of God, and what has been reached in modern studies of earth sciences? In a way that does not contradict the correct religious interpretations, the study relied on the analytical method, so it was one of the most important results of the study that the findings of modern science are the same as what was mentioned in the Holy Quran.
Keywords: Lose Earth; Science and Qur'an; Geological and Geomorphological Phenomena; Mountains Phenomenon; Detained Sea